DERMATOGLYPHIC PATTERNS OF LONG-TAILED MONKEY POPULATIONS ON MOUNT PENGSONG AND MOUNT PUSUK, LOMBOK - Rusli, Jessica Anabel; Soma, I Gede; Suardana, I Wayan (Buletin Veteriner Udayana, 2025)
Long-tailed macaques (Macaca fascicularis) on Lombok Island, living in groups on Mount Pengsong and Mount Pusuk, are separated by the densely populated city of Mataram. This geographical isolation may potentially affect the genetic diversity of the population, which can be known through dermatoglyphic studies. This research aims to identify and compare the dermatoglyphic patterns of the long-tailed macaque populations in both locations. The study used 34 samples of dermatoglyphics from the hands and feet of long-tailed macaques, consisting of 17 samples from Mount Pengsong and 17 samples from Mount Pusuk. Samples were collected using the transparent adhesive tape method, allowing for the identification of patterns and their frequencies, which were analyzed using chi-square tests. The results showed that four basic dermatoglyphic patterns were found: whorl, loop, open field, and arch. The dermatoglyphic pattern with the highest frequency in both Mount Pengsong and Mount Pusuk was the whorl pattern (35.5% and 36.2%, respectively). Meanwhile, the arch pattern was only found at Mount Pengsong. The chi-square analysis indicated no significant differences (p>0.05) in the frequencies of dermatoglyphic patterns between the two groups, suggesting that the city of Mataram does not cause significant genetic variation differences. It can be concluded that there are no significant differences in the patterns and frequencies of dermatoglyphics of long-tailed macaques between Mount Pengsong and Mount Pusuk, Lombok. Further research needs to be conducted using cluster analysis and with a larger sample.